Molecular evidence of zoonotic Babesia species, other than B. microti, in ixodid ticks collected from small mammals in the Republic of Korea. Issue 6 (7th September 2021) - Kim, Tae Yun; Kim, Seong Yoon; Kim, Tae‐Kyu; Lee, Hee IL; Cho, Shin‐Hyeong; Lee, Wook‐Gyo; Kim, Hyunwoo
Abstract: The occurrence of tick‐borne infectious diseases, including zoonotic babesiosis, has become a serious concern in recent years. In this study, we detected Babesia spp. using polymerase chain reaction (PCR) amplification of the 18S rRNA of the parasites isolated from ixodid ticks collected from small mammals in the Republic of Korea (ROK). Sequence analysis of the PCR amplicon revealed the presence of B. duncani, B. venatorum, B. capreoli/divergens, and, the most prevalent, B. microti in the ticks. The molecular phylogenetic analysis showed that the four species‐specific18S rRNA sequences clustered in four distinct clades. This is the first study to provide molecular evidence for the presence of zoonotic Babesia spp. other than B. microti in ticks in the ROK. Abstract : Babesiosis is an emerging malaria‐like disease caused by tick‐borne parasites. This study is the first to identify zoonotic Babesia spp. besides the predominant Babesia microti in ticks parasitizing on small mammals inhabiting different regions in the Republic of Korea. This indicates the need for nationwide surveillance of wildlife to prevent the occurrence of various zoonotic Babesia parasites.